HUBUNGAN SUPERVISI AKADEMIK KEPALA SEKOLAH TERHADAP PENINGKATAN KOMPETENSI PEDAGOGIK GURU DI SMK TR 2 SINAR HUSNI - Tiara Lubis; Salniati Nasution; Abdul Fattah Nasution; Bintang Ridzky Dwi Putra (PT PUBLIKASI INSPIRASI INDONESIA, 2026)
This study aims to examine the relationship between school principals' academic supervision and the improvement of teachers' pedagogical competence at SMK TR 2 Sinar Husni. Teachers' pedagogical competence is a key factor in enhancing the quality of learning and students' learning outcomes, thus requiring systematic professional development through academic supervision. This study uses a quantitative approach with a correlational design. The research subjects were all teachers at SMK TR 2 Sinar Husni, totaling 15 individuals. Data collection was conducted using a closed questionnaire that had been tested for validity and reliability. Data analysis was carried out with the help of the SPSS program through validity tests, reliability tests, normality tests, linearity tests, and Pearson Product Moment correlation tests. The results of the study indicate that school principals' academic supervision has a positive and significant relationship with teachers' pedagogical competence, with a correlation coefficient of 0.676 at the significance level. significance 0.01. These findings indicate that the better the implementation of the principal's academic supervision, the higher the teacher's pedagogical competence. This study recommends strengthening academic supervision that is continuous and developmental as a strategy to improve the quality of learning in vocational high schools.